The role of cytochromes P450 in the metabolism of selected antidepressants and anxiolytics under psychological stress - Nina Zemanova; Pavel Anzenbacher; Eva Anzenbacherova (Biomedical Papers, 2022)
In today's modern society, it seems to be more and more challenging to cope with life stresses. The effect of psychological stress on emotional and physical health can be devastating, and increased stress is associated with increased rates of heart attack, hypertension, obesity, addiction, anxiety and depression. This review focuses on the possibility of an influence of psychological stress on the metabolism of selected antidepressants (TCAs, SSRIs, SNRIs, SARIs, NDRIs a MMAs) and anxiolytics (benzodiazepines and azapirone), as patients treated with antidepressants and/or anxiolytics can still suffer from psychological stress. Emphasis is placed on the drug metabolism mediated by the enzymes of Phase I, typically cytochromes P450 (CYPs), which are the major enzymes involved in drug metabolism, as the majority of psychoactive substances are metabolized by numerous CYPs (such as CYP1A2, CYP2B6, CYP2C19, CYP2C9, CYP2A6, CYP2D6, CYP3A4). As the data on the effect of stress on human enzymes are extremely rare, modulation of the efficacy and even regulation of the biotransformation pathways of drugs by psychological stress can be expected to play a significant role, as there is increasing evidence that stress can alter drug metabolism, hence there is a risk of less effective drug metabolism and increased side effects.